(untitled) (Global Journal of Management and Business Research, 2020)
The main aim of the study was to assess moderating role of organizational citizenship behaviour on relationship between employee political skill and employee performance in Kenyan universities The study was grounded by social exchange theory The study used positivism paradigm explanatory research design simple and combination of random and stratified sampling on a target population of 6147 employees in selected universities in Kenya